Using methods of Multi-Criteria Decision Making to provide decision support concerning local bioenergy projects. (December 2019) - Lerche, Nils; Wilkens, Ines; Schmehl, Meike; Eigner-Thiel, Swantje; Geldermann, Jutta
Abstract: The public sector plays an important role in the German "Energiewende". Besides energy management in municipal properties the local government can also support the switch to renewable energy sources through a change in energy supply structures within in their region. Methods of Multi-Criteria Decision Making (MCDM) from Operations Research are helpful regarding that challenge, as they are able to assess the sustainability of local energy concepts, since they not only offer stakeholders the opportunity to participate, but also consider multiple conflicting criteria. In that way, the acceptance of local energy projects and the participation of stakeholders in the decision process are supported. The case study presented in this paper illustrates the results of a MCDM process employed to identify a sustainable bioenergy concept in a rural village in Lower Saxony, Germany. Our analysis revealed not only the opportunities and challenges associated with executing an MCDM process to support the realization of local bioenergy projects, but also discusses potential limitations of the methods. Highlights: The MCDM method PROMETHEE is applied for a sustainable bioenergy concept for a village. Opportunities and challenges associated with executing an MCDM process in real world case study are discussed. Potential steps of the structured decision process from MCDM which are suitable for residents' participation are identified. Project results which can be used in further applications, especially the developed criteria master-list, are presented.